Safety of Health IT : Clinical Case Studies - Agrawal, Abha (Springer International Publishing : Imprint : Springer, 2016)
This practical text provides an overview of the adverse consequences of health information technology (HIT) and its impact on patient safety. Specific cases of errors and risks related to various types of HIT are featured along with best practices for patient safety, workflows and organizational standards. The full impact of these challenges with meaningful solutions are openly examined. Written from a clinical perspective, healthcare professionals within multiple settings will find this timely book an invaluable resource to this essential and bourgeoning technology.